Optimizing Tobacco Chopping Machines with Information Technology Support for NU Millennial Farmers in Magelang - Bagus Prasetiyo, Angger; Hidayat, Muhammad Maksum; Zuhair, Alvin; Antika Prasetyaningtyas; Fakhril Husain; Ayuhikmatin Sekarjati, Kartinasari (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The lack of a regular maintenance schedule system and millennial farmers' lack of knowledge about maintaining tobacco shredding machines are the issues facing Nahdlatul Ulama (NU) in Magelang.  This scenario results in less than ideal shredded quality and frequent machine failures.  Enhancing farmers' knowledge and proficiency in maintenance, repair, and information technology use for scheduling machine maintenance is the aim of this community service project. The implementation approach consists of training in the use of basic digital programs to record and arrange maintenance schedules, hands-on machine maintenance and repair practice, and teaching through the supply of materials.  Thirteen ladies and seventeen males made up the 30 participants in the exercise. With participants' average comprehension rising from 22% prior to the activity to 86% following it, the outcomes discussed shown a notable improvement. It has been demonstrated that machine maintenance results in finer and more consistent shredded tobacco, and the application of information technology facilitates efficient and sustainable scheduling for participants.  The community service project was successful in enhancing the quality of the shredded output, maximizing machine performance, and motivating millennial farmers to be more flexible when it comes to using information technology in tobacco farming.